Recent advances in plant kinetochore research - Kozgunova, Elena (Frontiers in Cell and Developmental Biology, 2025)
Faithful chromosome segregation is crucial for cell division in eukaryotes, facilitated by the kinetochore, a multi-subunit protein complex that connects chromosomes to the spindle microtubules. Recent research has significantly advanced our understanding of kinetochore function in plants, including surprising findings about spindle assembly checkpoint, the composition of the inner kinetochore and unique kinetochore arrangement in holocentric Cuscuta species. Additionally, some kinetochore proteins in plants have been implicated in roles beyond chromosome segregation, such as cytokinesis regulation and involvement in developmental processes. This review summarizes recent insights into plant kinetochore biology, compares plant kinetochores with those of animals and fungi, and highlights key open questions and potential future directions in the field.